ҚАРАҚАЛПАҚСТАН РЕСПУБЛИКАСЫНДА ШАРЎАШЫЛЫҚТЫ БУННАН БЫЛАЙ ДА РАЎАЖЛАНДЫРЫЎ - Алламуратов, Б.; Алламуратова, З.; Қазақбаев, Б. (FAN va JAMIYAT, 2016)
The article deals with the issues of the development of the branch stock-breeding and increasing the quality of product in the farming and personal subsidiary facilities. The author of the article points out the necessity of organizing the contents and feeding and dealing with the tribe‘s work in cattle-breeding at the same time.